PENGARUH JENIS PELARUT TERHADAP AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN UBI JALAR PUTIH (Ipomoea batatas L) MENGGUNAKAN METODE MASERASI - Maria Kristin Gultom, Ade; Yusa, Ni Made; Sri Wiadnyani, Anak Agung Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2020)
This study aims to determine the effect of solvent types on antioxidant activity of white sweet potato leaf extract (Ipomoea batatas L) and to obtain the most appropriate type of solvent to produce white sweet potato leaf extract with high antioxidant activity. The experimental design uses in this research was Completely Randomized Design (CRD) with the treatment of solvent types methanol 80%, acetone 80%, ethanol 80% and aquades. The treatment was repeated four times so obtain 16 units of the experimental. Data were analysis of variance and followed by Duncan test if the treatment has a significant effect on measured variable. The results showed that, type of solvent had an obvious effect on antioxidant activity of white sweet potato leaves. Methanol was the best solvent in extract white sweet potato leaves with followed by yield was 32.11%, total flavonoids was 226.45 mg QE / g, total tannin was 16.58 mg TAE / g, vitamin C was 119.42 mg AAE / g and antioxidant activity was 82.42%.